The water purification system for the Daya Bay Reactor Neutrino Experiment. (April 2015) - Wilhelmi, J.; Bopp, R.; Brown, R.; Cherwinka, J.; Cummings, J.; Dale, E.; Diwan, M.; Goett, J.; Hackenburg, R.W.; Kilduff, J.; Littenberg, L.; Li, G.S.; et al.
Abstract: We describe the design, installation, and operation of a purification system that is able to provide large volumes of high purity ASTM (D1193-91) Type-I water to a high energy physics experiment. The water environment is underground in a lightly sealed system, and this provides significant challenges to maintaining high purity in the storage pools, each of which contains several thousand cubic meters. High purity is dictated by the need for large optical absorption length, which is critical for the operation of the experiment. The system is largely successful, and the water clarity criteria are met. We also include a discussion of lessons learned.